Capnography compared to pulse oximetry for early detection of respiratory compromise in non-intubated patients undergoing gastrointestinal endoscopy procedures: a systematic review protocol. (December 2016) - Holton, Jace; Flattery, Bryan
Abstract : Review question/objective: Does the use of capnography versus pulse oximetry increase the early detection of respiratory compromise and improve safety in non-intubated patients undergoing moderate sedation for gastrointestinal endoscopy procedures? Respiratory compromise will be detected by alveolar hypoventilation/hyperventilation (EtCO2 < 35 mmHg/EtCO2 > 50 mmHg), arterial oxygen desaturation (defined as a pulse oximetry reading of <95% for >5 s), visual assessments of abnormal ventilation including apnea detection and adverse respiratory events that involve the need for bag-mask ventilation.